Cut‐Offs and Diagnostic Performance of IgG Against Recombinant Aspergillus fumigatus Antigens in Differentiating ABPA From Asthma - Agarwal, Ritesh; Muthu, Valliappan; Sehgal, Inderpaul Singh; Prasad, Kuruswamy Thurai; Dhooria, Sahajal; Singh, Mani; Garg, Mandeep; Aggarwal, Ashutosh N.; Rudramurthy, Shivaprakash M.; Chakrabarti, Arunaloke (Mycoses, 2025)
ABSTRACT Background The diagnostic cut‐off values for IgG antibodies against recombinant Aspergillus fumigatus (rAsp) antigens in allergic bronchopulmonary aspergillosis (ABPA) remain unclear. Objectives To derive and validate diagnostic cut‐offs for IgG antibodies against rAsp f 1, f 2 and f 4 in ABPA and assess their diagnostic performance in distinguishing ABPA from asthma. Methods In this case‐control study, we prospectively enrolled consecutive subjects with asthma and ABPA. We measured serum IgG levels against rAsp f 1, rAsp f 2 and rAsp f 4 using a fluorescent enzyme immunoassay. Subjects were randomly split into derivation (50%) and validation (50%) cohorts. Cut‐offs were derived using receiver operating characteristic (ROC) curves and Youden's index. Additionally, we performed Bayesian latent class analysis (BLCA) using two‐component Gaussian mixture models to derive unbiased cut‐offs. Diagnostic performance was assessed using sensitivity, specificity and the area under the ROC curve (AUROC). Results Of 375 participants, 261 had ABPA and 114 had asthma. ROC‐derived AUROC values for rAsp f 1, f 2 and f 4‐IgG were 0.63, 0.47 and 0.52, while the cut‐off values were 10.1 mgA/L, 10.3 mgA/L and 10.5 mgA/L, respectively. Sensitivity was ≤ 42% for all antigens, while specificity exceeded 89%. BLCA yielded cut‐offs of 18.6, 14.9 and 13.7 mgA/L for f 1, f 2 and f 4, respectively, with similarly poor sensitivity and high specificity. Conclusions IgG antibodies against rAsp f 1, f 2 and f 4 exhibit high specificity but poor sensitivity in identifying ABPA, limiting their utility as standalone diagnostic markers.